Agreement Among Radiographs, Fluoroscopy and Bronchoscopy in Documentation of Airway Collapse in Dogs. (14th September 2015) - Johnson, L.R.; Singh, M.K.; Pollard, R.E.
Abstract : Background: Airway collapse is a common finding in dogs with chronic cough, yet the diagnosis can be difficult to confirm without specialty equipment. Hypothesis: Bronchoscopic documentation of tracheobronchial collapse will show better agreement with fluoroscopic imaging than with standard radiography. Animals: Forty‐two dogs prospectively evaluated for chronic cough. Methods: In this prospective study, three‐view thoracic radiographs were obtained followed by fluoroscopy during tidal respiration and fluoroscopy during induction of cough. Digital images were assessed for the presence or absence of collapse at the trachea and each lobar bronchus. Bronchoscopy was performed under general anesthesia for identification of tracheobronchial collapse at each lung segment. Agreement of imaging tests with bronchoscopy was evaluated along with sensitivity and specificity of imaging modalities as compared to bronchoscopy. Results: Airway collapse was identified in 41/42 dogs via 1 or more testing modalities. Percent agreement between pairs of tests varied between 49 and 87% with poor–moderate agreement at most bronchial sites. Sensitivity for the detection of bronchoscopically identified collapse was highest for radiography at the trachea, left lobar bronchi, and the right middle bronchus, although specificity was relatively low. Detection of airway collapse was increased when fluoroscopy was performed after induction of cough compared to during tidal respiration. Conclusions: Radiography and fluoroscopy are complementary imaging techniques useful in the documentation of bronchial collapse in dogs. Confirming the presence or absence of tracheal or bronchial collapse can require multiple imaging modalities as well as bronchoscopy.